Epidemic Algorithms for Reliability in Mobile Content-based Routing - Costa, Paolo (2002)
In recent years, scenarios characterized by an extreme degree of dynamicity and reconfiguration have attracted the attention of the research community. For instance, in mobile computing, devices can come and go continuously, e.g.,because they are free to move since connected through wireless links or because they are employed by a user, and hence plugged in and out of the infrastructure according to his/her movements. The situation is emphasized in pervasive computing whereby a component can often be replaced by another providing equivalent services, e.g., because a location change determined a different context populated by a different set of components, or because the component is no longer operational and is replaced by a new
Master Thesis, Politecnico di Milano. 2002. Advisors: Prof. Gian Pietro Picco and Prof. Gianpaolo Cugola